Event greening : is this concept providing a serious platform for sustainability best practice - Katzel, Charmaine Tzila (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2007.